Risk factors for perinatal arterial ischaemic stroke: a large case–control study. (5th September 2019) - Sorg, Anna‐Lisa; von Kries, Rüdiger; Klemme, Mathias; Gerstl, Lucia; Weinberger, Raphael; Beyerlein, Andreas; Lack, Nicholas; Felderhoff‐Müser, Ursula; Dzietko, Mark
Abstract : Aim: To identify maternal, obstetric, and neonatal risk factors related to perinatal arterial ischaemic stroke (PAIS) diagnosed within 28 days after birth and to understand the underlying pathophysiology. Method: For case and control ascertainment, we used active surveillance in 345 paediatric hospitals and a population‐based perinatal database for quality assurance of hospital care. We analysed complete cases of PAIS using logistic regression. Multivariate analysis was guided by a directed acyclic graph. Results: After exclusion of records with missing data, we analysed 134 individuals with PAIS and 576 comparison individuals. In univariate analysis, male sex, preterm birth (<37wks gestational age), small for gestational age (SGA), low umbilical artery pH (<7.1), low 5‐minute‐Apgar score (<7), multiple pregnancies, hypoxia, intubation/mask ventilation, nulliparity, Caesarean section, vaginal‐operative delivery, chorioamnionitis, and oligohydramnios were associated with an increased risk. Mutual adjustment yielded male sex (odds ratio [OR] 1.81; 95% confidence interval [CI] 1.20–2.73), multiple birth (OR 3.22; 95% CI 1.21–8.58), chorioamnionitis (OR 9.89; 95% CI 2.88–33.94), preterm birth (OR 1.86; 95% CI 1.01–3.43), and SGA (OR 3.05; 95% CI 1.76–5.28) as independent risk factors. Interpretation: We confirmed the increased risk in males and the role of chorioamnionitis and SGA for PAIS, pointing to the importance of inflammatory processes and fetal–placental insufficiency. Multiple birth and preterm birth were additional risk factors. What this paper adds: Chorioamnionitis and small for gestational age (SGA) precede perinatal arterial ischaemic stroke (PAIS). Chorioamnionitis and SGA are independent risk factors for PAIS. Inflammatory processes and fetal–placental insufficiency are the likely underlying mechanisms. Multiple birth and preterm birth are additional risk factors. What this paper adds: Chorioamnionitis and small for gestational age (SGA) precede perinatal arterial ischaemic stroke (PAIS). Chorioamnionitis and SGA are independent risk factors for PAIS. Inflammatory processes and fetal–placental insufficiency are the likely underlying mechanisms. Multiple birth and preterm birth are additional risk factors. This article is commented on by Chabrier and Sebire on page 413–414 of this issue.